2020
DOI: 10.1021/acs.inorgchem.9b03687
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Phenanthroline Ligands Containing Additional Donor Moieties and Their Resulting Cu(I) and Ru(II) Photosensitizers: A Comparative Study

Abstract: To bind or not to bind: Driven by the motivation to increase the (photo)stability of traditional Cu(I) photosensitizers, multidentate diimine ligands, which contain two additional donor sites, were designed. To this end, a systematic series of four 1,10phenanthroline ligands with either OR or SR (R = i Pr or Ph) donor groups at the 2 and 9 positions and their resulting hetero-and homoleptic Cu(I) complexes were prepared. In addition, the related Ru(II) complexes were also synthesized to study the effect of ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“… 24 26 Against this background, the development of ruthenium(II)- and iridium(III)-based photosensitizers continues to be important. 27 46 …”
mentioning
confidence: 99%
“… 24 26 Against this background, the development of ruthenium(II)- and iridium(III)-based photosensitizers continues to be important. 27 46 …”
mentioning
confidence: 99%
“…In line with our observations, Rentschler et al recently reported a series of [Cu(xantphos)(N^N)] + complexes in which the N^N ligands were 2,9-(RSCH 2 )-phen (R = phenyl or iso-propyl) but the authors did not report any intense absorption bands between 300 and 400 nm, despite the substituent containing a sulfur atom. 12 Excitation into the absorption bands around 400 nm of the [Cu(P^P)(N^N)] + complexes in deaerated solutions of THF or CH 2 Cl 2 at 293 K leads to luminescence (Fig. 5, S65-S67 and Table 3).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Light-emitting electrochemical cells (LECs) are devices for solidstate lighting, which were first described in 1995. 12 In these devices, a polymer (PLEC) or ionic transition metal complex (iTMC-LEC) is employed as a luminescent compound. Traditionally, iridium(III) and ruthenium(II) complexes have been used in iTMC-LECs due to their colour tunability (especially for Ir) and because their large spin-orbit coupling (SOC) leads to the mixing of singlet and triplet excited-states, thereby allowing for singlet as well as triplet exciton-harvesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tetrahedral diimine-Cu(I)-phosphine complex system, the emission state usually has a metal-toligand charge transfer (MLCT) characteristic, which is sensitive to the coordination environment. 7,8 In general, the excited state geometry is susceptible to Jahn-Teller geometric distortion and becomes a flattened conformation, facilitating relaxation to ground state through non-radiative decay pathways. 9 In general, the structural modification of common organic ligands such as phen or the design of new ligands are considered to be the most important methods for the synthesis of Cu(I) luminescent complexes.…”
Section: Introductionmentioning
confidence: 99%